Current Insights into Immunology and Novel Therapeutics of Atopic Dermatitis - Kader, Hidaya A. (Cells, 2021)
Atopic dermatitis (AD) is one of the most prevalent inflammatory disease among non-fatal skin diseases, affecting up to one fifth of the population in developed countries. AD is characterized by recurrent pruritic and localized eczema with seasonal fluctuations. AD initializes the phenomenon of atopic march, during which infant AD patients are predisposed to progressive secondary allergies such as allergic rhinitis, asthma, and food allergies. The pathophysiology of AD is complex; onset of the disease is caused by several factors, including strong genetic predisposition, disrupted epidermal barrier, and immune dysregulation. AD was initially characterized by defects in the innate immune system and a vigorous skewed adaptive Th2 response to environmental agents; there are compelling evidences that the disorder involves multiple immune pathways. Symptomatic palliative treatment is the only strategy to manage the disease and restore skin integrity. Researchers are trying to more precisely define the contribution of different AD genotypes and elucidate the role of various immune axes. In this review, we have summarized the current knowledge about the roles of innate and adaptive immune responsive cells in AD. In addition, current and novel treatment strategies for the management of AD are comprehensively described, including some ongoing clinical trials and promising therapeutic agents. This information will provide an asset towards identifying personalized targets for better therapeutic outcomes.